Design of wideband planar antenna with inverted I‐shaped tuning stubs for application in 5G, satellite communication, and Internet of Things. (26th April 2022) - Mukherjee, Kaushal; Mukhopadhyay, Subhadeep; Roy, Sahadev
Summary: In this article, a wideband planar antenna is proposed for 5G mobile communications, satellite communication, and Internet of Things (IoT)‐enabled applications. The proposed antenna consists of a rectangular radiating patch and two I‐shaped tuning stubs, excited by two I‐shape microstrip lines. The antenna of size (17 × 20 × 1) mm 3 is designed using FR4 material having a dielectric constant ( ε r ) of 4.4. Simulated results illustrate that the antenna operates with a radiation efficiency of 90% and a peak gain of 9.33 dBi. The achieved bandwidth of 161.54 GHz ranging from 31.6 to 193.14 GHz covers the licensed and planned bands of 5G communication (n257, n258, n259, n260, and n261). This antenna will support lower bands within 30 GHz (X, K, Ka, middle frequency bands), within 110 GHz (Q, U, V, W, F bands), and upper‐frequency bands up to 170 GHz (D‐band) used for satellite communication. The IoT framework is required to be updated, by ultra‐high‐speed antennas, which will improve the user experience in the fields like agriculture, communication, education, and transportation. A comparative study between the proposed antenna and other existing antennas with supporting results such as VSWR, impedance bandwidth, radiation efficiency, and gain is also presented in this work. Abstract : The proposed antenna of size (17 × 20 × 1) mm 3 is designed over FR4 material having ε r of 4.4. The antenna operates with radiation efficiency of 90% and a peak gain of 9.33 dBi. The achieved bandwidth of 161.54 GHz ranging from 31.6 to 193.14 GHz covers the licensed and planned bands of 5G communication (n257, n258, n259, n260, and n261) along with some satellite communication bands. The designed antenna is suitable IoT‐enabled applications like intelligent transportation system, and smart agriculture.